2013
DOI: 10.2108/zsj.30.178
|View full text |Cite
|
Sign up to set email alerts
|

Linking Mesohabitat Selection and Ecological Traits of a Fish Assemblage in a Small Tropical Stream (Tinggi River, Pahang Basin) of the Malay Peninsula

Abstract: Mesohabitat selection in fluvial fishes was studied in a small tropical stream of the Malay Peninsula. A total of 681 individuals representing 24 species were sampled at 45 stations within heterogeneous stream (ca. 1 km in length), in which water depth, water velocity, substrate size, and riparian canopy cover were measured as environmental variables. A canonical correspondence analysis (CCA) yielded a diagram that shows a specific mesohabitat selection of the fish assemblage, in which the species were plotted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This form-function relationship makes ecomorphological analysis a reliable methodology to infer many aspects of fish's niche, such as ecological interactions and habitat preferences (Gatz 1979a;Winemiller 1991;Langerhans et al 2003;Casatti and Castro 2006;Leal et al 2010). However, most studies relating morphology and spatial distribution of fishes in streams and rivers have defined the space in physiognomically homogeneous units (i.e., mesohabitat scale, such as riffles, runs, and pools; Rezende et al 2010;Kano et al 2013). Consequently, they probably have not detected niche segregation among several closely related species or morphological types, which in fact tend to occupy similar mesohabitats (e.g., riffles predominately occupied by depressed-body species, whereas pools inhabited by deep-body ones).…”
mentioning
confidence: 99%
“…This form-function relationship makes ecomorphological analysis a reliable methodology to infer many aspects of fish's niche, such as ecological interactions and habitat preferences (Gatz 1979a;Winemiller 1991;Langerhans et al 2003;Casatti and Castro 2006;Leal et al 2010). However, most studies relating morphology and spatial distribution of fishes in streams and rivers have defined the space in physiognomically homogeneous units (i.e., mesohabitat scale, such as riffles, runs, and pools; Rezende et al 2010;Kano et al 2013). Consequently, they probably have not detected niche segregation among several closely related species or morphological types, which in fact tend to occupy similar mesohabitats (e.g., riffles predominately occupied by depressed-body species, whereas pools inhabited by deep-body ones).…”
mentioning
confidence: 99%
“…Three "R" (rare: species usually localized within restricted geographical areas or habitats, or thinly scattered over a more extensive range) or "EN" (endangered: species facing a very high risk of extinction in the wild in the near future) species were not recorded in the most recent survey (Table 1), although several species noted by Othman et al (2003) as "not common" (NC) were represented by many individuals (Kano et al 2013b). It is clear that future habitat conservation and maintenance of fish diversity levels will necessitate continuous quantitative monitoring (see Kano et al 2013b). Othman et al (2003) and the present survey.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that these distinct characteristics of mesohabitats can select sh species according to their ecological requirements (e.g. diet, reproductive strategies, and substrate preference) (Berkman and Rabeni 1987; Teresa and Casatti 2012; Kano et al 2013) and body morphology (Gaston et al 2012;Bower and Piller 2015;Lujan and Conway 2015). For example, species that present a dorsoventrally depressed body are commonly found in the ri es, while the laterally compressed body is a prevalent characteristic of the species that inhabit the pools (Gaston et al 2012).…”
Section: Introductionmentioning
confidence: 99%